Group psychotherapy for obesity: a correlation between results of treatment and initial psychological testing - Henricus Wijsenbeek; Baruch Landau; Avner Elitsur (Arquivos de Neuro-Psiquiatria)
Twelve obese women, who had been refractory to Phenmethrazine hydrochloride and dietary treatment, were theated throughout one year with a combination of group psychotherapy and diet instructions. A significant correlation was found between the findings of the psychological testing and the results of group treatment. Patients who had been diagnosed by various tests as being neurotic responded much better to the combined treatment (as evaluated by weight-reduction and emotional improvement) than those patients which had been diagnosed as psychotics.